The Effectiveness of Online Collaborative Learning through Digital Platforms in Enhancing Students’ Communication Skills - Shanzey, Puspawati; Zaheera, Zaheera (Trigin Institute, 2025)
This research investigates the effectiveness of online collaborative learning using digital platforms in enhancing students’ communication skills, a core competency in 21st-century education. Communication skills are increasingly vital for academic success and professional readiness, making it essential to explore innovative pedagogical strategies that foster interaction in digital learning environments. Drawing on theories such as Vygotsky’s social constructivism and collaborative learning theory, this study examines how structured online collaboration contributes to the development of students’ ability to express ideas, negotiate meaning, and engage in constructive dialogue. The methodology employed a mixed-method approach, combining surveys, classroom observations, and interviews with students engaged in collaborative tasks via digital platforms. The results indicate that online collaborative learning significantly improves communication skills by promoting active participation, reflective practices, and peer-to-peer interaction. Furthermore, challenges such as unequal participation and technological barriers can be mitigated through scaffolding, role assignments, and clear communication guidelines. These findings align with previous studies while offering new insights into the role of reflective learning and instructional design in digital collaboration. The study contributes to both digital pedagogy and educational policy by highlighting the need for professional development programs for teachers, the integration of collaborative learning into curricula, and equitable access to digital resources. Ultimately, the research affirms that online collaborative learning is an effective pedagogical strategy not only for improving academic outcomes but also for equipping students with essential communication skills required in modern education and the global workforce.